The Role of Self-compassion to Depression in Teenagers Mediated by Emotion Regulation - Ade Meilasari; Muhana Sofati Utami (Faculty of Psychology, Universitas Gadjah Mada, 2022)
Adolescence is a stage of development in life that is full of emotional turmoil, conflict, and stress, of which often lead to teenagers’ vulnerability to depression symptoms. A potential serious case if the depression symptoms are not treated well includes risk of suicidal ideation and suicide behaviour. This research aims to investigate and test the role of self-compassion to depression symptoms in teenagers mediated by emotion regulation-cognitive reappraisal. Participants in this research were 627 teenagers (N=627) with an age range of 15-18 years old, including 508 girls (81%) and 119 boys (19%). Mediation analysis using Process by Andrew F. Hayes, model 4, shows that emotion regulation —cognitive reappraisal (p=0.001; p<0.05) mediates the role of self-compassion to depression symptoms in teenagers. Emotion regulation—cognitive reappraisal serves as a partial mediator to the role of self-compassion to depression symptoms. Teenagers with self-compassion treat themselves positively by realizing and accepting negative emotions that leads to reduction of these negative emotions. It improves the capability of cognitive reappraisal, that brings new interpretation towards a more positive view for reducing depression symptoms.